Teaching prudent antibiotic use on the go: a descriptive report on development, utilization and listener satisfaction of an educational podcast format for medical students and young professionals - Sandra Schneider; Clara Bergmann; Felicia Becker; Lukas Risse; Caroline Isner; Hartmut Stocker; Markus A. Feufel; Alina Röhrig; Oliver Kurzai; Thiên-Trí Lâm; Stefan Hagel; Mathias W. Pletz; et al. (Antimicrobial Resistance and Infection Control, 2024)
Abstract Background An important component in fostering the responsible use of antibiotics is training of new and future prescribers in this interdisciplinary topic. Because podcasts are playing an increasing role in medical education, we aimed to develop and evaluate a podcast format with practice and guideline-oriented learning content on antibiotic therapy for medical students and young medical professionals. Methods We developed the concept for the podcast with the direct involvement of medical students and medical experts with teaching experience. We used video conferencing when recording the episodes in order to have quick, easy, and nationwide access to the experts involved. We released an episode every 2 to 4 weeks on the popular podcast platforms. The podcast was promoted through mailing lists, social and print media, and at conferences. The evaluation of episodes was based on user data provided by the platforms and an anonymous feedback questionnaire linked to each episode in the podcast notes. Results Between December 2021 and December 2022 19 episodes of InfectEd: der Antibiotika-Podcast were released. The mean duration of an episode was 91 min. By March 9, 2023, a total of 38,829 downloads and streams had been recorded. The majority of users listened to the podcast on a mobile device. The average playing time per episode was 65%. The feedback questionnaire was completed 135 times. 60.7% of respondents were female, 38.5% male. The majority of respondents were in their twenties and thirties (66.7%). 31.1% were medical students, 25.9% were residents, and 25.2% were specialists. Listeners were asked to rate episodes on a scale from 1 to 6, where 1 was “very good” and 6 was “insufficient.” Ratings did not differ significantly between female and male respondents or between medical students and others. 118 respondents (87.4%) reported an increase in knowledge. Free-text feedback frequently emphasized clinical and also exam relevance. Conclusion Our podcast format, developed with a user-centered approach, was broadly distributed and has been well accepted by both medical students and physicians alike. It provides a large number of learners with low-threshold access to current, guideline-orientated content and could be a useful supplement to conventional teaching formats.